Enabling the 3D Printing of Metal Components in µ‐Gravity. Issue 10 (20th August 2019) - Zocca, Andrea; Lüchtenborg, Jörg; Mühler, Thomas; Wilbig, Janka; Mohr, Gunther; Villatte, Thomas; Léonard, Fabien; Nolze, Gert; Sparenberg, Marc; Melcher, Jörg; Hilgenberg, Kai; Günster, Jens
Abstract: As humanity contemplates manned missions to Mars, strategies need to be developed for the design and operation of hospitable environments to safely work in space for years. The supply of spare parts for repair and replacement of lost equipment will be one key need, but in‐space manufacturing remains the only option for a timely supply. With high flexibility in design and the ability to manufacture ready‐to‐use components directly from a computer‐aided model, additive manufacturing (AM) technologies appear extremely attractive. For the manufacturing of metal parts, laser‐beam melting is the most widely used AM process. However, the handling of metal powders in the absence of gravity is one prerequisite for its successful application in space. A gas flow throughout the powder bed is successfully applied to compensate for missing gravitational forces in microgravity experiments. This so‐called gas‐flow‐assisted powder deposition is based on a porous building platform acting as a filter for the fixation of metal particles in a gas flow driven by a pressure difference maintained by a vacuum pump. Abstract : A method is proposed to enable the additive manufacturing (AM) of metal powder by laser beam melting in microgravity conditions and is tested onboard parabolic flights. A gas flow throughout the powder bed is applied to compensate for the forces typically provided by gravity. This is the first step towards demonstrating the feasibility of AM of metals in space.